2023
DOI: 10.3390/electronics12051213
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Weather-Image Classification Combining VIT and a Dual Enhanced-Attention Module

Abstract: A weather-image-classification model combining a VIT (vision transformer) and dual augmented attention module is proposed to address the problems of the insufficient feature-extraction capability of traditional deep-learning methods with the recognition accuracy still to be improved and the limited types of weather phenomena existing in the dataset. A pre-trained model vision transformer is used to acquire the basic semantic feature representation of weather images. Dual augmented attention combined with convo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The results in Table 5 demonstrate that the proposed model achieved the highest performance. Specifically, on the MWD weather dataset, the model outperformed other excellent deep learning models, including AlexNet-feature fusion, VGG16-TL, MeteCNN, VGG16-GNet-SNN [11], L-CT, and VIT-DA [20], with improvements in F1-scores of 2.75%, 2.63%, 1.9%, 1.75%, 2.29%, and 0.75%, respectively. On the WEAPD weather dataset, the model exhibited F1-score improvements of 12.51%, 12.34%, 11.81%, 11.19%, 11.05%, and 9.89% compared to the same set of models.…”
Section: F Ablation Experiments and Comparison With Existing Meteorol...mentioning
confidence: 98%
See 3 more Smart Citations
“…The results in Table 5 demonstrate that the proposed model achieved the highest performance. Specifically, on the MWD weather dataset, the model outperformed other excellent deep learning models, including AlexNet-feature fusion, VGG16-TL, MeteCNN, VGG16-GNet-SNN [11], L-CT, and VIT-DA [20], with improvements in F1-scores of 2.75%, 2.63%, 1.9%, 1.75%, 2.29%, and 0.75%, respectively. On the WEAPD weather dataset, the model exhibited F1-score improvements of 12.51%, 12.34%, 11.81%, 11.19%, 11.05%, and 9.89% compared to the same set of models.…”
Section: F Ablation Experiments and Comparison With Existing Meteorol...mentioning
confidence: 98%
“…Li et al [20] conducted experiments and discovered that Transformer-based network architectures perform better on weather image datasets compared to CNN-based models. This research hypothesized that weather image data may have certain commonalities that can be learned more effectively by ViT-like networks.…”
Section: Performance Of Pre-trained Models and Fine-tuningmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that their implementation of Vision Transformer performed better than other current unsupervised techniques on splicing items. Li et al [11] implemented a model that combined a vision transformer and augmentation of images on the weather image classification problem. The research aimed to resolve the problems that lack the capability for feature extraction resulting from traditional deep learning models.…”
Section: Literature Reviewmentioning
confidence: 99%